2015
DOI: 10.1039/c5ew00125k
|View full text |Cite
|
Sign up to set email alerts
|

Emerging investigators series: the source and fate of pandemic viruses in the urban water cycle

Abstract: Several recent high profile outbreaks such as SARS, MERS, Ebola and avian influenzas draw attention to the continued risk of a deadly viral pandemic. In general, these enveloped viruses are not considered a major threat for the wastewater and water industries due to their assumed low concentrations in municipal wastewater and high susceptibilities to degradation in aqueous environments. A number of clinical reports, however, suggest that certain enveloped viruses are excreted in human feces during infection.Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
198
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(206 citation statements)
references
References 119 publications
3
198
0
5
Order By: Relevance
“…The conclusions of this study were drawn from experiments with naked viruses, which constitute the main fraction of enteric viruses. However, enveloped viruses, such as coronaviruses, can also be excreted in HEAM (97), and they are expected to behave differently due to the instability of the lipid bilayer under alkaline conditions. It was observed that phospholipids were cleaved at a rate of ϳ1 ϫ 10 Ϫ2 day Ϫ1 at 40°C and pH 9 (98), which is close to the RNA cleavage rate constant for similar conditions (1.6 ϫ 10 Ϫ2 day Ϫ1 at pH 9 and 37°C) (65).…”
Section: Discussionmentioning
confidence: 99%
“…The conclusions of this study were drawn from experiments with naked viruses, which constitute the main fraction of enteric viruses. However, enveloped viruses, such as coronaviruses, can also be excreted in HEAM (97), and they are expected to behave differently due to the instability of the lipid bilayer under alkaline conditions. It was observed that phospholipids were cleaved at a rate of ϳ1 ϫ 10 Ϫ2 day Ϫ1 at 40°C and pH 9 (98), which is close to the RNA cleavage rate constant for similar conditions (1.6 ϫ 10 Ϫ2 day Ϫ1 at pH 9 and 37°C) (65).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly in the case of RNA viruses, where higher nucleotide substitution rates can result in this rapid adaption and spreading in new host populations (Woolhouse and Gowtage-Sequeria, 2005). The potential of wastewater to be used for viral surveillance has been well discussed in the literature (Barras, 2018;O'Brien and Xagoraraki, 2019;Wigginton et al, 2015). Wastewater surveillance has already demonstrated promising results with the potential for retrospective prediction of disease outbreaks of hepatitis A and norovirus .…”
Section: Markers Of Pathogenic Organismsmentioning
confidence: 99%
“…This information points to a challenge of health consequences of environmental contamination, changing land use, infrastructure construction, habitat fragmentation, urbanization, and addressing demand for water, energy, and food, particularly when the cultural practices of those people most effected are not considered. Also important to consider is the role environmental engineering has in managing disease associated with pandemic viruses that may be found in the urban and agricultural water cycles (Wigginton et al, 2015).…”
Section: Fig 2 Contribution Of Communicable and Infectiousmentioning
confidence: 99%